Macro Sustainability Accounting: A New Way to Prepare Value Added Statement - Ali, Mohammed Ataallah; Abdullah, Salman Hussein (Journal of Economics and Administrative Sciences, 2021)
Traditional accounting takes only one dimension (economic) in calculating the value added of the company, and all other aspects (including environmental and social) are neglected, and despite the emergence of Sustainability Accounting and the interest of companies in preparing sustainability reports, these reports are suffering from many problems, including multiple metrics used in measuring companies (cash, quantity and lavish). In addition, these reports may reach dozens of pages in some companies and this causes the problem (information overload) which affects the qualitative properties of accounting information such as appropriate and relative, which requires the need to find a tool that can measure the Sustainability Unit of standard measurement, so easy to understand and use in comparison with standard reference (benchmark).The problem of research is the neglect of the cost of non-sustainability borne by society and the planet as a result of companies exercising their activities inefficiently, where these costs do not appear in the records of the companies causing them because of the common saying (that what cannot be measured cannot be managed and therefore cannot be held accountable) and this encourages companies to neglect sustainability.As a result, the research aims to find an objective way to measure the cost of non-sustainability incurred by society and the planet as a result of the inefficiency of these companies in the management of their activities, therefore, these costs can be charged to the companies that cause them, as this will play a significant role in changing the perception of corporate managers towards sustainability. The research led to a set of results, including the palaces of accounting tools (all branches) in measuring the cost of non-sustainability in cash.The research presented a set of recommendations, the most important of which is the need to take into account macro sustainability accounting by the stakeholders of this profession, and develop value-added statement using the technologies developed by the researcher (SVA$) because of its role in measuring the cost of non-sustainability critically, which will have a significant role in changing the corporate view for neglecting sustainability